Perception of e-learning in medical students and faculty during COVID time: A study based on a questionnaire-based survey - Sandip Meghnad Hulke; Santosh L Wakode; Avinash E Thakare; Rachna Parashar; Rajay N Bharshnakar; Ankur Joshi; Yuganti P Vaidya (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: With the emergence of COVID, we are forced to use e-learning in form of arranging online classes for students. Medical educators all over the world are conducting online classes for students. This study aimed to evaluate the perception of online learning among MBBS students and teachers through a questionnaire-based survey. MATERIALS AND METHODS: A cross-sectional study was done in the AIIMS, Bhopal. The study was based on questionnaire (online Google form) response received from 43 number of faculty and 156 number of students. STATISTICAL ANALYSIS USED: Chi-square test and unpaired t-test were used for statistical analysis using statistical software Systac 13.2. RESULTS: Handling software, technical issues, and lack of face-to-face interaction were more significant problems in students compared to faculty. The desire for the social site which causes disturbances in learning was a significant problem in the students compared to faculty. Giving and taking assessment problem was reported by 60% and 63.8% of faculty and students, respectively (P = 0.67). Both groups preferred the Google Classroom platform (P = 0.16). Students (65.3%) preferred audiovisual recording, while faculty (72%) preferred PowerPoint with narration. PowerPoint presentation without narration was the least preferred (10.8%). Both groups stressed the importance of training (P = 0.17) and infrastructure development (P = 0.85). Students, as well as faculty, strongly discouraged e-learning for practical/clinical teaching. CONCLUSIONS: Students, as well as faculty, have mixed reactions toward e-learning. Most importantly affected in the present scenario is practical/clinical teaching and assessment. Every attempt needs to be done to strengthen infrastructure and impart training to students and faculty.